426 Long non-coding RNA WNT5A-AS1 shows sex-dimorphic differences in survival for males with glioblastoma. (April 2022) - Miller, Aunay; Wang, Junwen; Loftus, Joseph; Tran, Nhan L
Abstract : OBJECTIVES/GOALS: The goal of this study is to evaluate the role of WNT5A and WNT5a-AS1 in sex-differences of GBM progression. In our preliminary studies, we found that a long non-coding RNA WNT5A-AS1 is overexpressed in male GBM patients. We also found that WNT5A-AS1s expression shows a negative correlation with overall survival within male patients. METHODS/STUDY POPULATION: We will define the mechanism by which WNT5A-AS1 regulates WNT5a-mediated glioma stem cell (GSC) maintenance by assessing the effects of inhibiting WNT5A-AS1 expression on transcriptional activity and stemness in GSCs. We will determine if there are distinct Wnt-signaling patterns in male and female isogenic murine astrocytes by examining the expression of downstream proteins in the Wnt signaling pathway and how inhibition of WNT5A-AS1 alters this expression. We will then examine the impact of WNT5A-AS1 on temozolomide (TMZ) resistance in-vitro and in-vivo. We will assess the cell viability and survival of GBM PDX cells upon treatment with TMZ in vitro. Next, we will assess the capacity of knockdown of WNT5A-AS1 to increase sensitivity to TMZ-induced cell death and prolong survival in vivo in intracranial models. RESULTS/ANTICIPATED RESULTS: We hypothesize that WNT5A-AS1 targets Wnt5a and regulates its expression. We anticipate that knockdown of WNT5A-AS1 will upregulate WNT5A expression. We also expect that inhibiting WNT5A-AS1 will alter GSC stem maintenance and functional effects. We expect to see an increase in downstream Wnt5a signaling proteins in males vs females when treated with exogenous Wnt5a. We hypothesize that knockdown of both, WNT5A-AS1 and WNT5A will alter the expression of downstream proteins. We hypothesize that knockdown of WNT5A-AS1 will decrease tumor growth and therapeutic resistance to TMZ while increasing survival in patient derived xenographs in vivo and in vitro. DISCUSSION/SIGNIFICANCE: This study will provide insight into the mechanisms underlying the difference in GBM onset and progression between male and female patients, which is clinically important. We will also characterize the biological role WNT5A-AS1 which is currently unknown to date and elucidate differential role of GSCs in GBM progression between male and female.